2007
DOI: 10.1108/00022660710732725
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter stability and control in the presence of windshear

Abstract: PurposeThis paper aims to present a theoretical method for analyzing the stability and control of a hingeless helicopter in the presence of windshear.Design/methodology/approachIn this paper, the stability and control of a hingeless helicopter in the presence of windshear are investigated. First, the rotary wing dynamic model considered is the one of flap‐pitch (including the elastic deformation of the control system)‐torsion coupling. The induced velocity nonuniform distribution derived from vortex theory is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One group of the current authors, Cao et al investigated the influence of wind shear on both helicopter flight characteristics (176,177) . It was found that left wind, tail wind and downdraft decrease the longitudinal stability, while the left wind, right wind and downdraft decrease the lateral/directional stability, as shown in Fig.…”
Section: Flight Dynamicsmentioning
confidence: 99%
“…One group of the current authors, Cao et al investigated the influence of wind shear on both helicopter flight characteristics (176,177) . It was found that left wind, tail wind and downdraft decrease the longitudinal stability, while the left wind, right wind and downdraft decrease the lateral/directional stability, as shown in Fig.…”
Section: Flight Dynamicsmentioning
confidence: 99%
“…On the other hand, nonlinear dynamics simulation, stability and control problems in helicopter design have been studied in Cao et al (2004) and Su et al (2007). Newman (2006) investigated the design characteristics of helicopters address to the requirements of efficiency in operations.…”
Section: Introductionmentioning
confidence: 99%